Practical Synthesis of Building Blocks for Oligosaccharides Containing the β-d-Galp-(1→3)-β-d-GlcpNAc Motif - Soliman, Sameh E.; Kováč, Pavol (Synthesis, 2014)
An efficient, new pathway for the synthesis of the title sequence has been developed. The sequence has been obtained as a glycosyl donor, β-d-Galp-(1→3)-β-d-GlcpNAc-1-SEt, or equipped with a linker (spacer) suitable for conjugation to other molecules, β-d-Galp-(1→3)-β-d-GlcpNAc-1-(OCH2CH2)3N3. Both disaccharides have been obtained in crystalline condition for the first time and fully characterized. The existing synthesis of the intermediate disaccharide glycosyl donor was improved by conducting the silver triflate mediated glycosylation under base-deficient conditions in the presence of 1,1,3,3-tetramethylurea and in the absence of molecular sieves.
Keywords: carbohydrates; oligosaccharides; synthetic methods; thioglycosides; protecting groups